Inter and intra-individual behavioral variability predicted by neural activity in the multiple demand network - Assem, Moataz. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2016., 2016)
A wide range of cognitive tasks consistently identify a Multiple Demand (MD) network in frontal and parietal brain regions. Its activity is closely linked to executive functions (EFs) such as attention, task switching, solving novel problems and manipulating information in the working memory. We here investigate the relation between MD neural activity and EFs using a large fMRI dataset (n=120). We examine this relation through two approaches (1) inter-individual variability, addressing several methodological challenges: We nd that MD activity - which varies substantially across individuals, but is consistent within individuals across time - can explain a substantial proportion of variance in individual performance on a spatial working memory task such that individuals who nd the task challenging, increase their MD activity substantially to improve their performance. This suggests that MD activity tightly re ects the executive demand of an individual. In the second approach we examine (2) trial-by-trial variability by employing three di erent models to fuse reaction time (RT) data with the BOLD time-series. We nd that BOLD amplitude increases with longer RTs. This is consistent with the ndings from the rst approach showing increased MD activity for slower individuals. Together both ndings support the view that within and between individual di erences are manifested in the same brain regions. These results have implications for (1) understanding brain processes of EFs through ID studies (2) given that ID in EF are largely genetically determined, genetic variability can be linked to the neural activity of the MD network as an intermediate stage to link genetics|Keywords : Multiple Demand, Executive Functions, Individual Di erences, Reaction time, Spatial Working Memory, Parametric modulation, fMRI.
Keywords: Executive functions (Neuropsychology); Spatial systems.; Magnetic resonance imaging.